Shared Values to Shared Action: A Global-Ethics Pathway for Youth Interfaith Tolerance in Indonesia: Dari Nilai Bersama ke Aksi Bersama: Jalur Etika Global untuk Toleransi Lintas Iman Generasi Muda di Indonesia - Casram Casram (CV. Media Publikasi Profesional, 2026)
This study aims to analyze a global-ethics-based model of religious tolerance developed by Peace Generation in West Java by explaining how global ethics is understood as a shared minimum value framework, how this framework is translated into tolerance-building programs, and how it strengthens youth tolerance in a plural society. Employing a qualitative case-study design, data were collected through in-depth interviews, participant observation, and document analysis (training modules, facilitation guidelines, program agendas, and activity reports), and were analyzed thematically through coding, categorization, and theme development to map program mechanisms and behavioral indicators of tolerance. The findings indicate that Peace Generation frames global ethics not as religious equalization, but as a form of public ethics emphasizing shared minimum values (e.g., respect for human dignity, empathy, justice, and non-violence), operationalized through a structured sequence of activities: core values training, dialogue ground rules (safe space), facilitated interfaith dialogue, reflective communication exercises, and interfaith humanitarian collaboration. As a result, youth tolerance is strengthened as an observable social competence, reflected in more respectful communication, reduced prejudice, more peaceful conflict management, and increased cross-identity cooperation. This study contributes to tolerance scholarship by offering practical guidance for educational institutions and youth communities to design more applicable and sustainable tolerance programs, while also informing local policy discussions on strengthening tolerance. The originality of this study lies in its operational, empirical mapping of the mechanism chain “global ethics → program design → changes in youth tolerance competencies” within a youth interfaith institution, thereby complementing prior studies that tend to remain normative or stop at index/survey mapping without detailing program steps and behavioral indicators.